El doble “subsuelo” ontológico de la interexistencialidad - Ivanoff-Sabogal, Christian (2025)
The aim of this research is to make explicit the ontological subsoil that underpins the approach to and treatment of Interexistentiality as set out in chapter IV of the first section of Being and Time. First, we clarify conceptually the indications about everydayness and “absorption” in the world that appear in the general introduction of the aforementioned chapter; this explains that Interexistentiality is by no means necessarily entangled with impropriety. Second, we show that the (first) ontological subsoil is the “radical difference” between existence and presenceat-hand [Vorhandenheit] in the broad sense as “objectuality”; this difference is the basis that sustains the necessity of posing the question of who is Dasein in a way that corresponds to the dynamism inherent of the “self”, which can be performed in an appropriate I-self or an improper one-self who is lost in the “others”. Thirdly, we show that the development of Interexistentiality is grounded in the (second) ontological subsoil: the “variety of Being”; there we argue that the three fundamental aspects of Interexistentiality, namely, being-with, the shared world and the latent preontological understanding of other Dasein, are only comprehensible in the light of the ontological interpretation of Dasein itself and the other as existences, especially distinguishing the latter from ontological determinations that do not belong originally to his “Being”.